A COMPREHENSIVE REVIEW OF TURBOCHARGER TURBINE EFFICIENCY ENHANCEMENT USING VARIABLE GEOMETRY SYSTEMS (VGS) - Qusai Noori Irmish1; Layth H. Jawad (Journals Park Publishing, 2025)
The continuous pursuit of higher efficiency, compact design, and lower emissions in internal combustion engines has positioned turbocharging as a critical enabler of engine downsizing and environmental compliance. Among the various boosting technologies, Variable Geometry Turbochargers (VGTs) have emerged as an advanced alternative to conventional Fixed Geometry Turbochargers (FGTs), offering superior adaptability across a wide operating range. This review provides a comprehensive evaluation of recent advancements in turbocharger turbine efficiency enhancement through the implementation of Variable Geometry Systems (VGS). The paper systematically compares traditional FGTs with modern VGT configurations, emphasizing aerodynamic optimization, actuator mechanisms, and control strategies. The study synthesizes recent experimental and computational developments that address challenges such as turbo lag, flow separation, and unsteady aerodynamic behavior. Various VGT architectures—including sliding nozzle, pivoting vane, and variable diffuser systems—are analyzed with respect to flow control, pressure ratio optimization, and turbine response. Additionally, the role of electric, hydraulic, and pneumatic actuators in improving real-time adaptability and control precision is critically reviewed. Emerging trends in model-based and artificial intelligence-assisted control systems are also discussed as enablers for next-generation engine platforms.
Keywords: Automotive turbocharging, Variable geometry turbocharger, Fixed geometry turbocharger.